PRACTICES OF THE GLOBAL HALLYU FANDOM AS A "POST-CREATOR". - Baek, Taehyun; Joo, Jiyoung (Kritika Kultura, 2026)
This study reconceptualizes global Hallyu fandom as a form of """Post-Creator""", where fans operate as cultural agents who reorganize affective structures and ethical codes within the algorithmic and economic conditions of platform capitalism. Drawing on Nicolas Bourriaud's concept of postproduction and Kang Sumi's formulation of the post-creator, this study positions fan practices as participatory or remixed acts while at the same time highlighting their role as politically and aesthetically significant interventions that reshape the meaning and circulation of cultural texts. Methodologically, this study conducts a comparative analysis of digital fan activities, including stage mixes, fan-subtitled translations, reaction videos, and performancebased challenges across platforms such as YouTube, TikTok, and X. Particular attention is paid to how localized practices in regions such as Southeast Asia and Latin America reflect distinct ethical and affective logics. The study further argues that these fan interventions represent strategic responses to the platform infrastructure, rather than isolated creative gestures, and that they embody a new mode of cultural authorship in the digital age. In doing so, it contributes to broader discussions on affective labor, platform governance, and the reconfiguration of cultural authority in transnational fandoms.